Answer:
416
Step-by-step explanation:
Answer:
(fog)(-2)=-5
Step-by-step explanation:
Given
f(x)= -7x+2
and
g(x)= √(x+3)
For finding (fog)(-2), we have to find (fog)(x) first
In order to find (fog)(x) we will put the value of g(x) in f(x) in place of x.
(fog)(x)= -7g(x)+2
Putting the value of g(x)
(fog)(x)= -7√(x+3)+2
We have to find (fog)(-2), so we have to put at the place of x in the composition
(fog)(-2)= -7√(-2+3)+2
(fog)(-2)= -7√1+2
= -7(1)+2
= -7+2
=-5
So,
(fog)(-2)=-5
Answer:
True
Step-by-step explanation:
Each x input has 1 y output
Answer:
Answer:
y = \frac{x}{36}y=
36
x
Step-by-step explanation:
Given
Length of string = x inches
Required
Determine the length in yards
Represent the equivalent length with y
Such that
y = x\ inchesy=x inches
Divide x by 36 to get equivalent in yards
y = \frac{1}{36} * xy=
36
1
∗x
y = \frac{x}{36}y=
36
x
Hence, the equivalent in yards is \frac{x}{36}
36
x